Why don't you believe me? Detecting deception in messages written by nonnative and native speakers. Issue 1 (17th November 2019) - Volz, Sarah; Reinhard, Marc‐André; Müller, Patrick
Summary: Detecting lies is crucial in numerous contexts, including situations in which individuals do not interact in their native language. Previous research suggests that individuals are perceived as less credible when they communicate in a nonnative compared with native language. The current study was the first to test this effect in truthful and fabricated messages written by native and nonnative English speakers. One hundred native English speakers judged the veracity of these messages, and overall, they proved less likely to believe and to correctly classify nonnative speakers' messages; differences in verbal cues between native and nonnative speakers' messages partly explained the differences in the judgments. Given the increased use of nonnative languages in a globalized world, the discrimination against nonnative speakers in veracity judgments is problematic. Further research should more thoroughly investigate the role of verbal cues in written and spoken nonnative language to enable the development of effective interventions.